ANALISIS PERILAKU KREDIT BERISIKO PADA MAHASISWA DENGAN MENGGUNAKAN TEORI PERILAKU TERENCANA YANG DIMODERASI OLEH LITERASI KEUANGAN - Artamefia Amy Herlintang (STKIP Subang, 2026)
This study aims to determine: (1) whether attitudes toward credit usage influence students' intention to use credit; (2) whether peers influence students' intention to use credit; (3) whether financial self-efficacy influences students' intention to use credit; (4) whether financial stress influences students' intention to use credit; (5) whether the intention to use credit mediates the relationship between the independent variables and students' risky credit behavior; and (6) whether financial literacy moderates the relationship between the intention to use credit and students' risky credit behavior. This is a quantitative study employing descriptive analysis. The population consists of students from the 2022–2025 cohorts who use credit services. The sample comprises 280 students selected using purposive sampling. Data were collected via a questionnaire using a 1–4 Likert scale. Data analysis utilized the Partial Least Squares (PLS) method within a Structural Equation Modeling (SEM) framework, involving outer and inner model analyses and hypothesis testing via bootstrapping. The results indicate that: (1) attitudes toward credit usage have a positive and significant effect on students' intention to use credit; (2) peers have a positive and significant effect on students' intention to use credit; (3) financial self-efficacy has a negative and significant effect on students' intention to use credit; (4) financial stress has a positive and significant effect on students' intention to use credit; (5) the intention to use credit mediates the effect of the independent variables on risky credit behavior; and (6) financial literacy does not moderate the relationship between the intention to use credit and students' risky credit behavior.